2015
DOI: 10.12740/pp/36178
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy of nonheterosexual people from the perspectives of therapists and patients – bilateral expectations and concerns

Abstract: Psychotherapists and LGB people basically agreed upon the therapeutic aims of psychotherapy. The adverse social situation of non-heterosexual people in Poland is a source of their concerns about the psychotherapeutic relations. On the other side the concerns of psychotherapists seem to correspond to some degree with the concerns of LGB people. They both reflect the society, which still struggles with heterosexism and homophobia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Other concepts towards which the psychiatrists were relatively unfavorable were, in decreasing order: people favoring homosexuality being ho-mosexual themselves, homosexuality as a mental disorder, homosexuality as immoral, avoiding homosexuals whenever possible, not allowing homosexuals to work with children, closing down homosexual bars, homosexuality endangering the institution of the family and homosexuals needing psychological treatment. In the Polish study by Iniewicz et al, although only 45.96% of the psychotherapists believed that homosexual orientation is not a developmental deviation, a small minority (3.54%) believed sexual orientation to be a mental disorder [14]. A detailed review of literature carried out by Stevenson in 2000 concluded that a gay man is no more likely than a straight man to engage in a sexual activity with children, and "cases of perpetration of sexual behavior with a prepubescent child by an adult lesbian are virtually nonexistent" [31].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other concepts towards which the psychiatrists were relatively unfavorable were, in decreasing order: people favoring homosexuality being ho-mosexual themselves, homosexuality as a mental disorder, homosexuality as immoral, avoiding homosexuals whenever possible, not allowing homosexuals to work with children, closing down homosexual bars, homosexuality endangering the institution of the family and homosexuals needing psychological treatment. In the Polish study by Iniewicz et al, although only 45.96% of the psychotherapists believed that homosexual orientation is not a developmental deviation, a small minority (3.54%) believed sexual orientation to be a mental disorder [14]. A detailed review of literature carried out by Stevenson in 2000 concluded that a gay man is no more likely than a straight man to engage in a sexual activity with children, and "cases of perpetration of sexual behavior with a prepubescent child by an adult lesbian are virtually nonexistent" [31].…”
Section: Discussionmentioning
confidence: 96%
“…This could be due to low self-reporting by patients due to stigma or due to psychiatrists' failure to ask specifically about sexual orientation during history taking [12,13]. In a study in Poland that aimed to assess expectations and concerns of psychotherapists towards non-heterosexual patients, it was reported that around a quarter (22.73%) of respondents had never seen a non-heterosexual patient [14].Often patients have no inhibitions about discussing their sexual orientation but want such topics to be initiated by a doctor [15].We should always try to include the question about sexual orientation in our routine history taking; that way we may be able to identify more homosexual patients during our routine clinical work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since minority stress is related to cultural variables in ethnic minorities, specific cultural variables could also be determined for gender and sexual minority populations, but more research is necessary to support this speculation. This Polish study among an SGM population and its clinicians [ 79 ] showed that those with a bisexual sexual identity were afraid of powerlessness in the face of the social situation of LGBTQA people. On the other hand, among homosexuals, the greatest concern was caused by psychotherapists’ attempts to change their sexual orientation.…”
Section: Discussionmentioning
confidence: 99%